Bringing it to the boil - Lovering, Matthew; Video Education Australasia (Australia : Video Education Australasia, 2004)
This instructive program explains the'moist heat' cooking methods such as boiling, blanching, poaching, steaming, stewing and braising, as well as microwave cooking. It also looks at and examines commercial food preparation and storage systems such as cook-chill, cook-freeze and sous-vide
Title from title screen
Executive producer, Mark McAuliffe ; editor, Paul Sutherland ; camera, Matthew Lovering
Narrator: Chelsea Bruland
Keywords: Cookery; Boiling (Cookery); Braising (Cookery); Steaming (Cookery); Poaching (Cookery); Stews; Food -- Storage